A Survey of Distributed Optimization and Control Algorithms for Electric Power Systems - Molzahn, Daniel K.; Dorfler, Florian; Sandberg, Henrik; Low, Steven H.; Chakrabarti, Sambuddha; Baldick, Ross; Lavaei, Javad (IEEE transactions on smart grid, 2017)
Historically, centrally computed algorithms have been the primary means of power system optimization and control. With increasing penetrations of distributed energy resources requiring optimization and control of power systems with many controllable devices, distributed algorithms have been the subject of significant research interest. This paper surveys the literature of distributed algorithms with applications to optimization and control of power systems. In particular, this paper reviews distributed algorithms for offline solution of optimal power flow (OPF) problems as well as online algorithms for real-time solution of OPF, optimal frequency control, optimal voltage control, and optimal wide-area control problems.